PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA MATERI PRINSIP KERJA SISTEM PENGAPIAN ELEKTRONIK - Elisnawati; Debora; Jhonni Rentas Duling (Steam Engineering, 2019)
From the results of observations and interviews with the teacher who taught the material understand the working principle of an electronic ignition system at SMK Negeri 2 Katingan Hilir, it’s known that the value of TBSM class XI students has not been fully achieved. This is related to the learning outcomes of some students who scored below 65, which did not meet the KKM score set by the school. This study aims to find out how student learning outcomes after applying the picture and picture learning model. The collection is done by using test methods in the form of pre-test and post-test, student response questionnaire, observation in the form of teacher activity sheets and student activity sheets, as well as documentation. The application of the picture and picture learning model to the material understanding the working principle of electronic ignition system of the students of Vocational High School 2 Katingan Hilir, which has been able to make students who take this model successfully obtain complete results and exceed the KKM set by the school which is 70 with 85.67 and lowest value 69 and classical completeness 95.83%. There is a significant increase in student learning outcomes